Corrosion and wear resistant marine propeller shaft and method of making same
Patent Information
- Application Number
- CN202311700342.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-11
AI Technical Summary
但其表面硬度仅为HV1600,而且其结构、材料成分以及磨损率也无法满足现代海洋船舶工业的实际应用需求
[0020]1.本发明在零件基体表面通过激光熔覆方法制备Mo/C/Fe粘结层和VMoZrWB/Mo工作层,Mo/C/Fe粘结层,可以减缓后续工作层与轮船尾轴零件基体材料之间的性能差异,改善两者之间的结构和性能上的匹配性能,增大激光熔覆层/基体材料之间的结合性能和工作层的耐冲击性能;VMoZrWB/Mo工作层中V元素提高了工作层的抗磨损性和耐腐蚀性能,Mo元素提高了工作层的硬度和强度,降低了工作层的摩擦系数,Zr元素对工作层起到固溶强化作用,提高了工作层的强度和抗磨损特性,W元素改善了工作层硬度和抗化学扩散性能,提高了工作层的抗氧化性能和耐腐蚀性。各个元素之间的相互协同使VMoZrWB/Mo工作层具有较高的硬度,优异的耐腐蚀性、化学稳定性和耐摩擦磨损性能,能够提高轮船尾轴零件表面的耐腐蚀性能和耐磨性能。
Smart Images

Figure CN117684161B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of marine machinery parts manufacturing technology, specifically relating to a method for preparing a corrosion-resistant and wear-resistant ship stern shaft. Background Technology
[0002] Seawater is a highly complex corrosive environment, containing various inorganic salts, organic matter, dissolved gases, suspended solids, colloids, and organisms. Due to the large amount of sodium chloride in seawater, and the strong corrosive activity of chloride ions, steel corrosion in marine environments is extremely severe. Ships and other marine machinery operate at sea for extended periods, making corrosion a critical problem. This not only affects the ship's performance, increases production costs, and reduces efficiency, but also poses significant safety hazards.
[0003] The stern shaft is the last section of the ship's transmission system. Its bow flange is bolted to the intermediate shaft flange; the stern end is conical and used to mount the propeller. The stern shaft is typically forged from high-quality carbon steel. The stern shaft operates under harsh conditions, being susceptible to seawater corrosion and subjected to twisting and alternating bending stress, leading to various serious malfunctions, including corrosion, abrasion, excessive wear, burning, and rust. Cracks may appear at the transition points and keyways of the stern shaft due to fatigue, vibration, and impact. The journals and shaft shaft may also corrode due to poor sealing. Therefore, improving the performance of ship stern shaft components is one of the key technologies for the development of modern marine shipbuilding.
[0004] Due to the excellent properties of boride ceramics, such as high hardness, corrosion resistance, and wear resistance, it is expected that preparing boride ceramic coatings on the surface of parts can improve their surface performance and service life, thereby extending the service life of marine hydraulic motors. Chinese invention patent CN114875401A discloses a surface modification method for a high-pressure hydraulic pump gear shaft: after quenching, high-temperature tempering, and rough machining, a Mo / C / Fe bonding layer and a Mo2FeB2 / Mo working layer are prepared on the surface of the hydraulic pump gear shaft blank using laser cladding, followed by stress-relief tempering, semi-finishing, and finishing. However, its surface hardness is only HV1600, and its structure, material composition, and wear rate cannot meet the actual application requirements of modern marine shipbuilding industry. Summary of the Invention
[0005] This invention provides a method for preparing a corrosion-resistant and wear-resistant stern shaft for ships. First, a Mo / C / Fe composite bonding layer is prepared on the surface of the component's substrate material. This can mitigate the performance differences between the subsequent working layer and the substrate material of the stern shaft component, improving the structural and performance matching between the two. The VMoZrWB / Mo boride working layer has high hardness, excellent corrosion resistance, chemical stability, and friction and wear resistance, which can improve the corrosion resistance and wear resistance of the surface of the stern shaft component.
[0006] The technical solution of this invention is as follows:
[0007] In a first aspect, a corrosion-resistant and wear-resistant stern shaft for ships is disclosed, comprising a stern shaft component body, an adhesive layer, and a working layer arranged sequentially from the inside out. The adhesive layer is a Mo / C / Fe adhesive layer, and the working layer is a VMoZrWB / Mo working layer.
[0008] Preferably, the Mo / C / Fe binder layer is made of Mo, C and Fe composite powder with a particle diameter of 50-100 nm and a weight percentage of 15-25%, 30-40% and 35-55%, respectively.
[0009] Preferably, the VMoZrWB / Mo working layer uses VMoZrWB and Mo powders. The VMoZrWB powder has a particle diameter of 70-130 nm, and the atomic percentage content of each element in the VMoZrWB powder is: V: 50-55 at.%, Mo: 15-20 at.%, Zr: 10-15 at.%, W: 3-6 at.%, B: 10-12 at.%. The Mo powder has a particle diameter of 50-100 nm, and the weight percentages of VMoZrWB and Mo powders are 60-75% and 25-40%, respectively.
[0010] Secondly, a method for preparing the corrosion-resistant and wear-resistant stern shaft of a ship is disclosed. After the stern shaft part blank is forged, quenched, tempered at high temperature, and rough machined, a Mo / C / Fe bonding layer and a VMoZrWB / Mo working layer are prepared on the surface of the part using a laser cladding method. Then, stress-relief tempering, semi-finishing, and finishing are performed. The specific steps include the following:
[0011] (1) Machining of ship stern shaft parts blanks: forging;
[0012] (2) Heat treatment and machining of ship stern shaft parts: quenching of base blank → high temperature tempering → rough machining;
[0013] (3) Surface pretreatment of ship stern shaft parts: remove oil and oxide film from the surface of the parts, rinse and dry;
[0014] (4) Cladding Mo / C / Fe bonding layer: Argon protective gas is introduced at a flow rate of 11L / min-14L / min; laser cladding of Mo / C / Fe bonding layer, the cladding process parameters are: laser power 1400-1500W, scanning speed 220-260mm / min, laser spot diameter 1.6-2.5mm, overlap rate 50-60%, cladding thickness 0.7-1.5mm;
[0015] (5) Cladding VMoZrWB / Mo working layer: Argon protective gas is introduced at a flow rate of 18L / min-23L / min; laser cladding of VMoZrWB / Mo working layer, the cladding process parameters are: laser power 2300-2600W, scanning speed 260-280mm / min, laser spot diameter 2.5-3.0mm, overlap rate 30-40%, cladding thickness 2-4mm;
[0016] (6) Post-processing: After the workpiece cools down, stress-relieving tempering → semi-finishing → finishing.
[0017] The Mo, C and Fe composite powders used in the laser cladding Mo / C / Fe bonding layer are ground and mixed in a ball mill for 120-150 minutes.
[0018] The VMoZrWB and Mo powders used in the cladding VMoZrWB / Mo working layer are ground and mixed in a ball mill for 200-240 minutes.
[0019] Compared with the prior art, the present invention has the following advantages:
[0020] 1. This invention prepares a Mo / C / Fe bonding layer and a VMoZrWB / Mo working layer on the surface of a component substrate using a laser cladding method. The Mo / C / Fe bonding layer can mitigate the performance differences between the subsequent working layer and the substrate material of the ship stern shaft component, improve the structural and performance matching between the two, and increase the bonding performance between the laser cladding layer and the substrate material, as well as the impact resistance of the working layer. In the VMoZrWB / Mo working layer, V element improves the wear resistance and corrosion resistance of the working layer, Mo element improves the hardness and strength of the working layer and reduces the coefficient of friction, Zr element plays a solid solution strengthening role in the working layer, improving the strength and wear resistance of the working layer, and W element improves the hardness and chemical diffusion resistance of the working layer, as well as the oxidation resistance and corrosion resistance. The synergistic effect between the various elements gives the VMoZrWB / Mo working layer high hardness, excellent corrosion resistance, chemical stability, and friction and wear resistance, which can improve the corrosion resistance and wear resistance of the surface of the ship stern shaft component.
[0021] 2. The surface modification method of this invention can improve the adhesion performance between the laser cladding layer and the substrate, and the surface hardness of the parts can reach HV2000 or above, which is nearly 3 times higher than the hardness of traditional surface carburizing heat treatment (HV620-675). The wear rate is reduced by 60-75%, the corrosion resistance is improved, and the effective coating process time is only 1-3% of that of the traditional carburizing process. This reduces the maintenance and upkeep costs of ship stern shafts and extends the service life of marine ship stern shaft parts. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the surface structure of the ship stern shaft part prepared according to Embodiment 1 of the present invention. In the figure, 1 is the ship stern shaft part substrate; 2 is the Mo / C / Fe bonding layer; and 3 is the VMoZrWB / Mo working layer.
[0023] Figure 2 This is the surface optical morphology of the ship stern shaft part prepared in Embodiment 1 of the present invention.
[0024] Figure 3 This is a comparison chart of the average wear rate of the ship stern shaft part prepared in Embodiment 1 of the present invention and the traditional carburized part. Detailed Implementation
[0025] This invention provides a corrosion-resistant and wear-resistant stern shaft for ships, comprising a stern shaft component body, an adhesive layer, and a working layer arranged sequentially from the inside out. The adhesive layer is a Mo / C / Fe adhesive layer, which uses Mo, C, and Fe composite powder with a particle diameter of 50-100 nm and weight percentages of 15-25%, 30-40%, and 35-55%, respectively. The working layer is a VMoZrWB / Mo working layer, which uses VMo... ZrWB and Mo powders, wherein the VMoZrWB powder has a particle diameter of 70-130 nm, and the atomic percentage content of each element in the VMoZrWB powder is: V: 50-55 at.%, Mo: 15-20 at.%, Zr: 10-15 at.%, W: 3-6 at.%, B: 10-12 at.%; the Mo powder has a particle diameter of 50-100 nm, and the weight percentages of VMoZrWB and Mo powder are 60-75% and 25-40%, respectively.
[0026] Example 1
[0027] This embodiment provides a surface modification method for a ship's stern shaft, where the base material is 20CrMnTi medium-carbon alloy steel. After forging, quenching, high-temperature tempering, and rough machining, the stern shaft blank is clad with a Mo / C / Fe bonding layer and a VMoZrWB / Mo working layer on its surface using laser cladding. Following this, stress-relief tempering, semi-finishing, and finishing are performed. The specific steps include the following:
[0028] (1) Stern shaft blank processing: forging of stern shaft blank, forging radius R4.
[0029] (2) Heat treatment and machining of ship stern shaft parts: quenching of base blank (870℃, oil cooling) → high temperature tempering (600℃, holding time: 130min; cooling method: air cooling) → rough machining (surface roughness Ra25μm, machining dimensions: tolerance lower limit -2mm).
[0030] (3) Surface pretreatment of ship stern shaft parts: remove oil and oxide film from the surface of the parts, rinse and dry.
[0031] (4) Preparation of Mo / C / Fe composite powder: Mo, C and Fe composite powder is used, with a particle diameter of 65 nm and a weight percentage of 20%, 35% and 45%, respectively. The Mo / C / Fe powder is ground and mixed in a ball mill for 120 min.
[0032] (5) Preparation of VMoZrWB / Mo powder: VMoZrWB / Mo powder is used. The particle diameter of VMoZrWB powder is 70nm. The atomic percentage content of each element in VMoZrWB powder is: V: 55at.%, Mo: 20at.%, Zr: 10at.%, W: 5at.%, B: 10at.%; the particle diameter of Mo powder is 50nm. The weight percentages of VMoZrWB and Mo powder are 65% and 35%, respectively. The VMoZrWB / Mo composite powder is ground and mixed in a ball mill for 200min.
[0033] (6) Cladding Mo / C / Fe bonding layer: Argon protective gas is introduced at a flow rate of 11L / min; laser cladding of Mo / C / Fe bonding layer, the cladding process parameters are: laser power 1420W, scanning speed 225mm / min, laser spot diameter 1.6mm, overlap rate 55%, cladding thickness 0.7mm.
[0034] (7) Clad VMoZrWB / Mo working layer: Argon protective gas is introduced at a flow rate of 18L / min; laser cladding of VMoZrWB / Mo working layer, the cladding process parameters are: laser power 2350W, scanning speed 265mm / min, laser spot diameter 2.6mm, overlap rate 35%, cladding thickness 2.5mm.
[0035] (8) Post-processing: After the cladding layer cools down, stress-relief tempering is performed (520℃, air cooling), and semi-finishing is performed on a lathe (surface roughness Ra1.6μm, machining allowance 0.2mm) → finish machining is performed on a lathe (surface roughness Ra0.8μm, machining dimensions to the tolerance range).
[0036] The surface morphology of the tail shaft part with laser-clad VMoZrWB / Mo coating obtained in this embodiment is as follows: Figure 2 As shown, the microhardness of the coating surface reached HV2015 (testing equipment: HVS-1000A micro Vickers hardness tester, load 1.0N), which is nearly three times the surface hardness of the traditional carburizing process (HV650). Under the same friction test conditions (HRT-A02 ball-and-disc friction and wear tester, reciprocating linear motion, grinding balls are WC balls with a surface hardness of HRC55-60, load 100N, friction speed 10mm / s, test time 30min), the wear rate of the laser-clad VMoZrWB / Mo layer prepared by this method was 2.64×10⁻⁶. -6 mm 3 The wear rate of parts treated with this method is reduced by 57% compared to that treated with traditional carburizing processes, as shown in Figure 3. Furthermore, the effective coating process time is only about 1 hour, which is only 2% of the processing time of traditional carburizing. In addition, the tail shaft parts prepared by this method show no obvious corrosion even after 20 months of use, while tail shaft parts prepared by traditional heat treatment processes show severe corrosion and rust after only 11 months of use, affecting the normal operation of the tail shaft.
[0037] Example 2
[0038] This embodiment provides a surface modification method for a ship's stern shaft, where the base material is 20Mn2B medium-carbon alloy steel. After forging, quenching, high-temperature tempering, and rough machining, the stern shaft blank is clad with a Mo / C / Fe bonding layer and a VMoZrWB / Mo working layer on its surface using laser cladding. Following this, stress-relief tempering, semi-finishing, and finishing are performed. The specific steps include:
[0039] (1) Stern shaft blank processing: forging of stern shaft blank, forging fillet R4-R5.
[0040] (2) Heat treatment and machining of ship stern shaft parts: quenching of base blank (870℃, water cooling) → high temperature tempering (565℃, holding time: 160min; cooling method: air cooling) → rough machining (surface roughness Ra25μm, machining size: tolerance lower limit -2mm).
[0041] (3) Surface pretreatment of ship stern shaft parts: remove oil and oxide film from the surface of the parts, rinse and dry.
[0042] (4) Preparation of Mo / C / Fe composite powder: Mo, C and Fe composite powder is used, with a particle diameter of 90 nm and a weight percentage of 25%, 40% and 35%, respectively. The Mo / C / Fe powder is ground and mixed in a ball mill for 150 min.
[0043] (5) Preparation of VMoZrWB / Mo powder: VMoZrWB / Mo powder is used. The particle diameter of VMoZrWB powder is 115nm. The atomic percentage content of each element in VMoZrWB powder is: V: 55at.%, Mo: 20at.%, Zr: 10at.%, W: 5at.%, B: 10at.%; the particle diameter of Mo powder is 90nm. The weight percentages of VMoZrWB and Mo powder are 75% and 25%, respectively. The VMoZrWB / Mo composite powder is ground and mixed in a ball mill for 240min.
[0044] (6) Cladding Mo / C / Fe bonding layer: Argon protective gas is introduced at a flow rate of 13L / min; laser cladding of Mo / C / Fe bonding layer, the cladding process parameters are: laser power 1480W, scanning speed 250mm / min, laser spot diameter 2.4mm, overlap rate 55%, cladding thickness 1.4mm.
[0045] (7) Clad VMoZrWB / Mo working layer: Argon protective gas is introduced at a flow rate of 22L / min; laser cladding of VMoZrWB / Mo working layer, the cladding process parameters are: laser power 2550W, scanning speed 275mm / min, laser spot diameter 2.9mm, overlap rate 35%, cladding thickness 3.5mm.
[0046] (8) Post-processing: After the cladding layer cools down, stress-relief tempering (525, air cooling) is performed → semi-finishing is performed in the machining center (surface roughness Ra3.2μm, machining allowance 0.5mm) → finish machining is performed in the machining center (surface roughness Ra1.6μm, machining dimensions to the tolerance range).
[0047] The VMoZrWB / Mo laser cladding layer prepared in this embodiment achieved a surface microhardness of HV2072, which is nearly twice that of the surface hardness of parts prepared by traditional carburizing processes (HV650). Under the same friction test conditions, the wear rate of the laser cladding VMoZrWB / Mo layer prepared by this method was 2.42 × 10⁻⁶. -6 mm 3 / N·m, which reduces the wear rate of parts by 60% compared to the traditional carburizing process.
[0048] Although the present invention has been described in detail with reference to the accompanying drawings and preferred embodiments, the invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for manufacturing a corrosion-resistant and wear-resistant ship stern shaft, characterized in that, The stern shaft of a ship includes a stern shaft component body, an adhesive layer, and a working layer arranged sequentially from the inside to the outside. The adhesive layer is a Mo / C / Fe adhesive layer, and the working layer is a VMoZrWB / Mo working layer. The Mo / C / Fe binder layer uses a composite powder of Mo, C, and Fe, with a particle diameter of 50 mm. The weight percentage of 100nm is 15%. 25%, 30 40% and 35 55%; the VMoZrWB / Mo working layer uses VMoZrWB and Mo powders, wherein the VMoZrWB powder particles have a diameter of 70 mm. The atomic percentage content of each element in the 130nm VMoZrWB powder is: V: 50 55at .%, Mo: 15 20at .%, Zr: 10 15at .%,W:3 6at .%, B: 10 12 at .%; Mo powder particle diameter is 50 mm. At 100nm, the weight percentages of VMoZrWB and Mo powders are 60%. 75% and 25 40%; The method for preparing the corrosion-resistant and wear-resistant ship stern shaft involves forging, quenching, high-temperature tempering, and rough machining of the ship stern shaft part blank. Then, a Mo / C / Fe bonding layer and a VMoZrWB / Mo working layer are prepared on the surface of the part using laser cladding. Following this, stress-relief tempering, semi-finishing, and finishing are performed. Specifically, the method includes the following steps: (1) Machining of ship stern shaft parts blanks: forging; (2) Heat treatment and machining of ship stern shaft parts: Quenching of base blank → High temperature tempering → Rough machining; (3) Surface pretreatment of ship stern shaft parts: remove oil and oxide film from the surface of the parts, rinse and dry; (4) Cladding Mo / C / Fe bonding layer: Argon protective gas is introduced at a flow rate of 11 L / min 14L / min; Laser cladding of Mo / C / Fe bonding layer, cladding process parameters: laser power 1400 1500W, scan speed 220 260 mm / min, laser spot diameter 1.6 2.5mm, overlap rate 50 60%, cladding thickness 0.7 1.5mm; (5) Cladding VMoZrWB / Mo working layer: Argon protective gas is introduced at a flow rate of 18 L / min 23 L / min; laser cladding of VMoZrWB / Mo working layer, cladding process parameters are: laser power 2300 2600W, scanning speed 260 280 mm / min, laser spot diameter 2.5 3.0mm, overlap rate 30 40%, cladding thickness 2 4mm; (6) Post-processing: After the workpiece cools down, stress-relieving tempering → semi-finishing → finishing; The Mo, C, and Fe composite powders used in the laser cladding Mo / C / Fe adhesive layer were ball-milled and mixed for 120 seconds. 150 min; The VMoZrWB and Mo powders used in the cladding VMoZrWB / Mo working layer were ball-milled and mixed for 200 seconds. 240 minutes.
Citation Information
Patent Citations
Surface modification method for gear shaft of high-pressure hydraulic pump
CN114875401A
Method for producing spherical powder of high-entropy alloy boride
RU2808748C1
